Az Antonescu-kormány első lépései magyar diplomáciai jelentések tükrében - Lakatos, Artur (Közép-Európai Közlemények, 2014)
This paper is presenting documents from the National Archives of Hungary, which are dealing with the first image and early diplomatic activities of the Antonescu government from Romania, through the eyes of the Hungarian diplomacy. Preceded by a short introduction, which introduce the reader into the circumstances of general Antonescu’s rise to power, the documents represent a good synthesis on what were the major concerns of Hungarian state politicians concerning Antonescu and his allies, the violent and incalculable Iron Guard. Works of diplomatic representations of Hungary in Bucharest, Rome and Berlin, these reports are containing synthetic description of the first Antonescu government, and in details, events which accompanied Antonescu’s first diplomatic visits in his quality of Prime Minister and Conducator in Rome and Berlin. These documents probably will not change the already existing image of the Antonescu government, but will bring an important contribution for understanding its role in the regional system of international relations during the first years of World War II.